Interventional therapy for partial anomalous pulmonary venous connection with dual drainage - Saurabh Kumar Gupta; Anita Saxena; Rajnish Juneja (Wolters Kluwer Medknow Publications, 2017)
A 6-year-old boy presented with dual drainage of left upper pulmonary vein, with connection to innominate vein inaddition to its normal connection to the left atrium. Despite relief of aortic stenosis at the age of 3 years, significant left to right shunt persisted. The dual drainage allowed successful percutaneous closure of the levoatriocardinal vein without obstruction to the pulmonary venous flow to the left atrium.